2014
DOI: 10.1039/c3cc48773c
|View full text |Cite
|
Sign up to set email alerts
|

Facile synthesis of nanostructured CuCo2O4 as a novel electrode material for high-rate supercapacitors

Abstract: CuCo2O4 nanostructures were synthesized through a facile solution combustion method. Electrochemical investigations demonstrate a novel electrode material for supercapacitors with remarkable performance including high-rate capability, high-power density (22.11 kW kg(-1)) and desirable cycling stability at different current densities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
121
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(123 citation statements)
references
References 22 publications
(14 reference statements)
2
121
0
Order By: Relevance
“…This phenomenon is resulted from the effect of internal resistance. Internal resistance is reported to increase with increasing charge-discharge cycle [68][69][70]. At higher resistance, less charges flow causes less current flow which result a decrease in C s value as shown in Table 7.…”
Section: Cyclic Voltammetrymentioning
confidence: 82%
“…This phenomenon is resulted from the effect of internal resistance. Internal resistance is reported to increase with increasing charge-discharge cycle [68][69][70]. At higher resistance, less charges flow causes less current flow which result a decrease in C s value as shown in Table 7.…”
Section: Cyclic Voltammetrymentioning
confidence: 82%
“…This advanced configuration for maguey-like CuCo 2 O 4 nanowires electrode schematically illustrated in Fig. 6b, which distinguishes from the capacitance increasing of those normal nanostructure in previous reports [17,25,26,29], where only the nanowires provided single channel for charge transition. Based on these observations, maguey-like CuCo 2 O 4 nanowires electrode has the following characteristics beneficial to capacitance improvement.…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…Pendashteh et al reported CuCo 2 O 4 nanoparticles exhibit a high capacitance of 338 F g -1 at 1 A g -1 [25].…”
mentioning
confidence: 99%
“…The redox peaks in CV of Fig. 4(a & c) are attributed to faradic reaction involving Co 4+ /Co 3+ and M 2+ /M + with OH À ions [30]. The redox peak of the electrode materials can be attributed to the following reactions [3,[31][32][33].…”
Section: Electrochemical Studiesmentioning
confidence: 97%